Effect of Physalis angulata leaf extract cream on Interleukin-4, Interleukin-6, and Immunoglobulin-E in mice with induced atopic dermatitis - Dhany Prafita Ekasari; Santosa Basuki; Wuriandaru Kurniasih; Herwinda Brahmanti; Aunur Rofiq (Faculty of Medicine, Universitas Trisakti, 2023)
BackgroundThe prevalence of atopic dermatitis (AD) and allergic or irritant contact dermatitis has been increasing significantly in the general population. Interleukin- 4 (IL-4), interleukin-6 (IL-6), and immunoglobulin E (IgE) play a key role in the pathogenesis of AD. Physalis angulata (PA) leaves reportedly have anti-inflammatory effects by impeding IL-4, IL-6, and IgE. This study aimed to evaluate the effect of PA leaf extract cream on IL-4, IL-6, and IgE using 2,4-dinitrochlorobenzene (DNCB) to induce AD-like skin inflammation in a mice model. MethodsThis study used an experimental design involving 30 BALB/c mice, that were randomized into 3 groups: 1) control group receiving no treatment; 2) Vehicle treatment group receiving vehicle cream preparation; 3) PA treatment group receiving 10% PA leaf extract cream after induction of AD-like skin inflammation by DNCB. After 30 days, tissue samples were extracted from the skin lesions to measure IL-4 and IL-6 levels, and serum to measure IgE using ELISA. One-way Anova, Kruskal-Wallis and Mann-Whitney tests were used to analyze the data. ResultsGroup 3 (PA treatment) had significantly lower IL-4 (281.15 ± 43.14 pg/mL) than group 2 (vehicle cream treatment) (388.89±135.88 pg/ml) (p=0.001). However, although IL-6 and IgE levels were lower in group 3 than in group 2, the differences were statistically not significant (p=0.096 and p=0.479 respectively). ConclusionThere were lower levels of IL-4, IL-6, and IgE in the group receiving PA leaf extract cream than in the group receiving vehicle cream preparation. Therefore, PA leaf extract cream may have therapeutic potential in AD.